Hematological, biochemical, coagulation profiles of patients with cerebral palsy and epilepsy on the background of taking valproic acid in the perioperative period - V. V. Evreinov (Вестник анестезиологии и реаниматологии, 2024)
Introduction. Valproic acid is one of the commonly prescribed basic anticonvulsants for the treatment of epileptic seizures in children with cerebral palsy. Its active metabolites can cause hematological and coagulation disorders, cause valproate-induced steatohepatitis.The objective was to assess the level of hematological, biochemical and coagulation blood parameters in the perioperative period in children with severe forms of cerebral palsy during the treatment of concomitant epilepsy with valproic acid.Materials and methods.  A prospective cohort study included 72 patients with cerebral palsy, spastic hip dislocations, who underwent reconstructive interventions on hip joints. Depending on the presence of concomitant epilepsy, the patients were divided into two groups. Perioperative laboratory blood parameters, complication incidence, the duration of stay in the intensive care unit and hospitalization were assessed.Results.  In patients with epilepsy, the number of platelets in the blood was lower compared to the control group. The level of alkaline phosphatase before and after surgery in 34 % of children who took anticonvulsants exceeded the maximum value of the norm. Groups differed in terms of peri -operative coagulogram and thromboelastography. The frequency of complications in patients with epilepsy ranged from 0.08 % to 16.2 %.Conclusions.  Basic therapy with valproic acid in children with severe forms of cerebral palsy and concomitant epilepsy is associated with a tendency to hypocoagulation, but was not accompanied by clinically significant thrombocytopenia or coagulopathy during hip surgery. Taking valproic acid drugs in patients with cerebral palsy and epilepsy was not accompanied by an increase in serum liver enzymes at all stages of  observation, which minimized the likelihood of valproate-induced hepatotoxicity. Anticonvulsant therapy with valproate in children with severe forms of cerebral palsy and concomitant epilepsy did not increase the potential risk of complications in the perioperative period, did not affect the duration of stay of patients in the intensive care unit and hospitalization.